Liberalizing international trade in services: Challenges and opportunities for developing countries - Matthias Lücke; Dean Spinanger (Institut für Weltwirtschaft (IfW), 2004)
Several developments in international trade in services impact strongly on developing countries: First, the world-wide diffusion of information technologies (IT) has created new export opportunities for developing countries in IT services. Second, the recently proclaimed Millennium Development Goals for poverty reduction can only be attained if key services are provided more efficiently in developing countries - particularly through the liberalization of service imports. Third, in the ongoing Doha Development Round (DR) of trade negotiations, developing countries are asked to formally commit to liberalizing their service imports under the terms of the General Agreement on Trade in Services (GATS). Developing countries will benefit from liberalizing service imports if liberalization enhances competition on the supply side. This is typically the case for producer services, such as domestic and international transport, financial services, and telecommunications. The lifting of restrictions on the market access by foreigners (including through direct investment) will often improve service quality or lower prices and thereby enhance the international competitiveness of downstream industries. In Doha Development Round negotiations, therefore, developing countries may find it useful to commit to liberalizing imports of producer services. By contrast, the benefits of import liberalization are less clear for some consumer services where supply is subject to network monopolies (e.g., water and energy distribution) or demand is constrained by poverty (health care, education). Here, achieving a socially optimal level of supply may require carefully calibrated government policies, possibly with international donor support. For developing countries, such sectors should not be priority areas for commitments on service imports under the GATS. Most service exports by developing countries, especially IT services transmitted electronically, face few import barriers in industrialized countries. However, under the GATS, service exports may also be delivered through temporary movement of natural persons, e.g., developing country nationals working in industrialized countries without becoming residents there. If Doha Development Round negotiations were to increase opportunities for such temporary labor migration, the benefits to developing countries could be huge.
Keywords: 330; Internationaler Dienstleistungsverkehr; GATS; Außenhandelsliberalisierung; Entwicklungsländer